2022
DOI: 10.1111/mec.16826
|View full text |Cite
|
Sign up to set email alerts
|

Rapid shifts in thermal reaction norms and tolerance of brooded coral larvae following parental heat acclimation

Abstract: Thermal priming of reef corals can enhance their heat tolerance; however, the legacy effects of heat stress during parental brooding on larval resilience remain understudied. This study investigated whether preconditioning adult coral Pocillopora damicornis to high temperatures (29°C and 32°C) could better prepare their larvae for heat stress. Results showed that heat-acclimated adults brooded larvae with reduced symbiont density and shifted thermal performance curves. Reciprocal transplant experiments demonst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 123 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that apoptotic and antiapoptotic processes coexist within cells (Kvitt et al, 2016;Majerova et al, 2021). The balance between anti-apoptotic and pro-apoptotic genes within the cell dictates the ultimate apoptotic rate (Kvitt et al, 2016;Majerova et al, 2021;Jiang et al, 2023). This also suggests that P. lutea under acute stress at 14°C was in a pre-bleaching stage.…”
Section: Low-temperature Stress Limits the Calcification Of P Luteamentioning
confidence: 96%
“…Previous studies have shown that apoptotic and antiapoptotic processes coexist within cells (Kvitt et al, 2016;Majerova et al, 2021). The balance between anti-apoptotic and pro-apoptotic genes within the cell dictates the ultimate apoptotic rate (Kvitt et al, 2016;Majerova et al, 2021;Jiang et al, 2023). This also suggests that P. lutea under acute stress at 14°C was in a pre-bleaching stage.…”
Section: Low-temperature Stress Limits the Calcification Of P Luteamentioning
confidence: 96%
“…Among these reef restoration approaches, branching coral species have emerged as the preferred candidates due to their fast growth rates, higher nursery survival rates, the ease of handling large numbers of fragments in the nurseries, esthetic appeal, and the capacity to quickly create complex environments. Considering future environmental contexts, these reef restoration approaches may be further optimized by incorporating naturally heat-resistant corals [ 103 , 104 ], or those engineered to be more environmentally resilient via selective breeding, coral chimerism, epigenetics, and/or microbiome manipulation [ 105 , 106 ], or by artificially increasing structural complexity [ 107 ]. This optimization can be employed to design reef-of-tomorrow restoration in a degraded coral reef area, featuring a different consortia of coral reef taxa compared to the pre-degradation state.…”
Section: Using Environmental Considerations To Innovate Restoration A...mentioning
confidence: 99%